Konsultasi dan Adaptasi Manajemen Mutu Madrasah Berbasis Riset Kearifan Lokal Dalam Pengembangan Potensi Lokal di MTs Nurul Fajri - Ibrahim Ibrahim; M. Sirozi; KMS. Badaruddin; Yuniar Yuniar; Hidayat Hidayat; Sinka Afmitiani; Ade Riani (Pusat Riset dan Inovasi Nasional, 2022)
The quality of a product is one of the most important factors in increasing the competitiveness of a product. Total Quality Management is an approach used in running a business to maximize the competitiveness of an organization through continuous improvement of its services, products, processes and environment. Total Quality Management according to Josep M. Juran Quality is the suitability of a product use (Fitness For Use) which is to meet customer needs and satisfaction. Josep is often referred to as